Media Massa beserta Ideologinya dalam Proses Hegemoni - Akhmad Yani Surachman (Media Nusantara, 2021)
The media does not only influence society from the content it conveys, but also by the characteristics of the media itself. This shows the power and influence of the media (medium) on society, not just the content of the message. Media and ideology always go hand in hand. Referring to McLuhan that the medium is the message, the media is the message itself, and the message is part of the hegemonic process. However, there is no single ideology promoted by the popular media. However, the mass media, have a tendency to determine human behavior, attitudes and lifestyles in a narrow perspective according to their standards. The tendency which then marginalizes or ostracizes people who are different from the norms as presented by the media